DAMPAK PEMBELAJARAN ONLINE PADA MATA PELAJARAN SOSIOLOGI DI MASA PANDEMI COVID-19 DI SMA 4 PANDEGLANG (Tanjungpura University, 2021)
The Covid-19 pandemic has changed all activities around the world including the world of education due to the widespread impact of the covid-19 learning process activities in schools have been temporarily suspended and diverted to online or online learning, however, many parents have pros and cons related to online learning. Sociology learning in the midst of Covid-19 has experienced changes where there should be direct social interaction in problem-solving (face-to-face) between teachers and students turning online due to social distancing restrictions where this learning is difficult to practice for students. The purpose of this study was to determine the impact of online learning on sociology subjects at SMAN 4 Pandeglang. This research method uses qualitative methods, namely the form of interviews and observations. Based on the results of the interviews conducted, it can be seen that online learning still experiences problems such as some students do not have cellphones, unstable internet networks in remote areas, and learning media that are less supportive. In addition, students also sometimes struggle to do the assignments given by the teacher because the assignments given are too many, but students do not understand the learning material